Potential applications of cyanobacteria: Spirulina platensis filtrates and homogenates in agriculture - Godlewska, K. (World J Microbiol Biotechnol, 2019)
In the present paper, products obtained from a blue-green microalga Spirulina platensis filtrate (applied for seed soaking and for foliar spray) and homogenate (used for seed coating) were tested in the cultivation of radish. Their effect on length, wet mass, multielemental composition and the greenness index of the radish leaves was examined. Multi-elemental analyses of the algal products, and radish were also performed using inductively coupled plasma-optical emission spectrometry (ICP-OES). The best soaking time, concentrations of filtrate and doses of homogenate were established. The longest and heaviest plants were observed for homogenate applied at a dose of 300 µL per 1.5 g of seeds and 15% of filtrate applied as foliar spray. The highest chlorophyll content was found in the group treated with 100 µL of homogenate and 5% of filtrate. In the case of soaking time, the longest plants were in the group where seeds were soaked for 6 h, but the heaviest and greenest were after soaking for 48 h. The applied algal products increased the content of elements in seedlings. Obtained results proved that algal extracts have high potential to be applied in modern horticulture and agriculture. The use of Spirulina-based products is consistent with the idea of sustainable agriculture that could help to ensure production of sufficient human food to meet the needs of rising population and protection of the environment.